Digital-Based Transformation of Quranic Teaching to Improve Community Competence in the Technological Era: A Case Study in Bandung Regency - Asep Muhyiddin; Solihin Solihin; Caca Handika (Prodi Magister Sosiologi UIN Sunan Gunung Djati Bandung, 2026)
This study aims to analyze the digital transformation of Qur’anic teaching to enhance community competence in the technological era, focusing on three majelis ta’lim (Islamic study groups) in Bandung Regency. Key concepts include digital literacy, blended learning, community-based education, and Islamic education based on adab (ethics). The research employed a participatory approach with observation, interviews, focus group discussions, and simple questionnaires. The subjects comprised women from majelis ta’lim and Generation Z, representing two major social groups in digital adoption. The findings reveal that the use of Qur’an applications, video conferencing, and YouTube-based distribution of learning materials improves access, flexibility, and interactivity in religious education. Challenges include limited digital infrastructure, generational gaps in digital literacy, and concerns over the decline of spiritual blessings inherent in face-to-face learning. This study recommends a digital Qur’anic learning model that balances traditional values with technological innovation. Practical implications highlight the importance of continuous mentoring, strengthening teachers’ digital capacity, and developing creative, verified digital content. Contribution: This research contributes to the development of digital literacy theory in Islamic education, enriches the literature on the role of majelis ta’lim in the digital era, and proposes a practical implementation model that can be replicated in other contexts.